Work-Life Balance and Job Satisfaction Among Employees at PT Paguntaka Cahaya Nusantara Ambon Branch - Frenklyn Steve Wenno; Susana Prapunoto (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
In an era of increasingly fierce competition, work development, and ever-increasing demands, maintaining employees’ work-life balance has become a strategic imperative for every company. The purpose of this study was to determine the relationship between work-life balance and job satisfaction in employees of PT Paguntaka Cahaya Nusantara Ambon branch. This study used a quantitative, correlational approach. Data were collected through distributing scales to 234 employees selected using an accidental sampling technique. The data obtained is analysed using Pearson’s correlation analysis. The results of this study indicate a positive and significant relationship between work-life balance and job satisfaction (r = .470, p < .01). The greater the perceived balance between work and personal life, the higher employees’ job satisfaction. This finding underscores the importance of company policies in supporting employees’ work-life balance to increase job satisfaction, which, in turn, will contribute to productivity, employee retention, and overall organisational performance. Keywords: work-life balance, job satisfaction, employees